Anti-Americanism in Contemporary Indonesia - Saiful Mujani (Studia Islamika, 2005)
This paper attempts to explore these two basic arguments. To that end we need first to discuss what is meant by "anti-Americanism," then what is meant by "unjust American foreign policies," and thirdly what is meant by "civilization" in the context of Indonesian Muslim society. "Anti-Americanism" in the international context is an individual or group attitude or action that reflects a feeling of dislike, hatred or intolerance toward America as a nation, or America as defined by the attitudes or behavior of the American government toward other countries. It is not easy to decide how to measure these anti-American attitudes or actions.DOI: 10.15408/sdi.v12i2.588